Afiks se- sebagai Afiks Derivasional dalam Bahasa Indonesia - Ailsa Zevaulima Dilivia; Khotimatul Rosidah; Bakdal Ginanjar (Madah: Jurnal Bahasa dan Sastra, 2023)
This study aims to describe the changes in the form of affixation in Indonesian language. This research is a qualitative descriptive type. The data of this research are in the form of sentences containing the prefix se- which are sourced from online newspapers, anthologies of short stories, and scientific books. Data were collected by means of listening method and note-taking technique which were then analyzed  sequentially by using distributional method, immediate constituent technique, deletion, replacing, and expansion techniques. The results of data analysis were presented by means of informal and formal methods. It was concluded that the derivational affix se- functions to form nouns from adjectives and verbs, numerals from adjectives and nouns, adjectives from verbs, and adverbs from verbs and nouns.